Pengaruh Pengetahuan dan Sikap Ibu yang Bekerja Dari Rumah Selama Work Form Home Terhadap Perilaku Anak Dalam Menjaga Kebersihan Rongga Mulut dimasa Pandemi Covid-19 - Desy Purnama Sari (Andalas Dental Journal, 2020)
The covid-19 pandemic is hitting the world including Indonesia. Work from home (WFH) is one of the Indonesian goverment's policy to prevent the spread of covid-19. The mother’s knowledge, attitude, and practice regarding oral health are the important indicator that reflect their children's oral health behaviour. Objective: to analyse the relationship of mother's knowledge and practice to the children's oral health behaviour during WFH in the covid-19 era. Method: This is a cross-sectional study used the purposive sampling techniques. Thirty respondents were selected by the following criterias: women; have children aged 12 months until 12 years; work outside the home as employees; and willing to participated in this study. Respondents were instructed to fill the self-administered questionnaire through the Google Form application. Data of the mother's knowledge, practice and the children's behaviour were collected, then analysed by computerizing system. Results: Good knowledge and positive practice about oral health was represented by each 73,3% respondents. Approximately 76,7% of the children had satisfaction behaviour and only 23,3% had unsatisfaction of oral health behaviour. The study shows a statistical significant relationship of mothers’ knowledge level (p=0,003) and mother's practices (p=0,044) to their children's behavior toward oral health care. Conclusion: There is a significant relationship between mother's knowledge and practices to the children's oral health behaviour. Good knowledge and positive attitude of mothers determined the satisfaction of children's behaviour in the oral health care, especially int the covid-19 era.